Is there a gap in the gap? Regional differences in the gender pay gap - Boris Hirsch; Marion König; Joachim Möller (Institute for the Study of Labor (IZA), 2009)
In this paper, we investigate regional differences in the gender pay gap both theoretically and empirically. Within a spatial oligopsony model, we show that more densely populated labour markets are more competitive and constrain employers' ability to discriminate against women. Utilising a large administrative data set for western Germany and a flexible semi-parametric propensity score matching approach, we find that the unexplained gender pay gap for young workers is substantially lower in large metropolitan than in rural areas. This regional gap in the gap of roughly ten percentage points remained surprisingly constant over the entire observation period of thirty years.
urn:nbn:de:101:1-20090622132
Keywords: J16; J42; J71; 330; Gender pay gap; urban-rural differences; matching; monopsonistic discrimination; Lohndifferenzierung; Regionale Lohnstruktur; Stadt; Ländlicher Raum; Deutschland